Penilaian Kinerja Karyawan dengan Menggunakan Metode Behaviorally Anchor Rating Scale dan Management By Objectivitas di PT. Cahaya Riau - Al-Ghozy, Athaullah Ahmad; Nur, Muhammad; Suherman, Suherman; Lubis, Fitriani Surayya; Hamdy, Muhammad Ihsan (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to determine the performance of production employees at PT. CR uses two assessment methods, namely Behaviorally Anchor Rating Scale (BARS) and Management By Objectives (MBO). PT. CR experienced a significant decline in performance during the period March 2023 to February 2024, where production did not reach the target of 7,000 tons per month. The main problems faced by the company are employee indiscipline, late attendance, and high levels of absenteeism without clear explanation. In this research, the BARS method is used to assess employee work behavior based on a structured assessment scale, while the MBO method is used to determine individual work targets objectively. The research results show that the application of performance appraisal using these two methods is able to provide a more comprehensive evaluation of employee performance and offer solutions to improve their performance. By implementing this method, companies can carry out structured employee performance assessments using the BARS method and strategies for achieving monthly production targets using the MBO method.